2022
DOI: 10.1186/s40798-022-00416-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and Musculoskeletal Measurements as Risk Factors for Running-Related Injury in Non-elite Runners: A Systematic Review and Meta-analysis of Prospective Studies

Abstract: Background Running-related injury (RRI) is highly prevalent among recreational runners and is a key barrier to participation. Atypical lower limb alignment and mechanical function have been proposed to play a role in development of lower extremity injury. The purpose of this study was to investigate relationships between incidence of running-related injury (RRI) in non-elite runners with biomechanical and musculoskeletal variables. Methods A system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…In addition, ~7 % of our participants left the study due to an injury. Typically, the rate of running-related injuries (RRIs) among novice runners is ~30 % [58], and obesity is a major risk factor for RRIs [59]. Since the rate of progression in training volume and intensity may contribute to the risk of RRI [60], an approach to running through periodizing POL or THR may represent an efficacious strategy to increase adherence to training while reducing both RRI and dropout rate over a long period of training in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ~7 % of our participants left the study due to an injury. Typically, the rate of running-related injuries (RRIs) among novice runners is ~30 % [58], and obesity is a major risk factor for RRIs [59]. Since the rate of progression in training volume and intensity may contribute to the risk of RRI [60], an approach to running through periodizing POL or THR may represent an efficacious strategy to increase adherence to training while reducing both RRI and dropout rate over a long period of training in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the theory of Root et al ,1 two meta-analyses found a weak causal link between flat feet and medial tibial stress syndrome, patellofemoral pain syndrome and non-specific lower limb overuse injuries, but no other conditions 2 3. Furthermore, one systematic review and one meta-analysis revealed that flat feet are not risk factors of running-related injuries 4 5. These reviews collectively challenged the notion that flat feet are a substantial risk factor for a wide range of musculoskeletal conditions.…”
Section: Flat Feet and Musculoskeletal Injuriesmentioning
confidence: 95%
“…Peterson et al [ 122 ] found in a meta-analysis that running injuries may be associated with reduced knee extensor strength ( p = 0.03) and lower hip adduction velocity during running ( p = 0.04). Running injuries may also be associated with an imbalance between stronger hip abductors and weaker hip adductors [ 123 ].…”
Section: Resistance Exercise For Reducing the Risk Of Running-related...mentioning
confidence: 99%